I MANAJEMEN KELUARGA BERDASARKAN AL-QUR'AN DAN HADIS - Indah Kusharyati; Zahid, Moh; Nurhadi, Ali (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2024)
Family is the smallest order that must be managed. Family management is defined as the process of organizing, planning, directing, and controlling family resources (including finances, time, energy, and skills) to achieve common family goals. In managing a family, many bases are used, one of which is based on the Qur'an and Hadith. Based on a literature review, especially the Qur'an and Hadith, there are six basic concepts of Islamic family management, namely leadership in the family, education, justice and compassion, cooperation and responsibility, finance, and problem solving in the family. In addition, there are several theoretical foundations of Islamic family management that can be applied based on the interpretation of Al Misbah, namely the value of monotheism, the importance of justice and equality in husband and wife relationships, Islamic education and child care, the importance of managing the economy, the balance of the world and the hereafter, and patience and fortitude in facing the tests of family life.